Vapor contribution to the time dependence of the effective diffusion coefficient in partially filled porous glasses - Farrher, Germán; Ardelean, Ioan; Kimmich, Rainer (Diffusion Fundamentals, 2007)
NMR microscopy of silica glasses with micrometer pores (Vitrapor#5) partially filled with water reveal heterogeneous distributions of the liquid on a length scale much longer than the pore dimension. This heterogeneity, which is not observed in MRI of saturated samples, is attributed to the spatial variation of the granular microstructure. As a consequence of the inhomogeneous filling degree, the effective transverse relaxation time varies, which in turn leads to NMR imaging contrasts. Since the spatial distribution of the transverse relaxation time prevents reliable measurements with the standard pulsed gradient stimulated echo technique (PGStE), a combination of the fringe field stimulated echo method (FFStE) on the one hand and the magnetization grid rotating frame imaging technique (MAGROFI) on the other was employed in our investigations. Using this combination four decades of the diffusion time from 100 μs to 1 s could be probed. The comparison of the experimental data with Monte Carlo simulations on a model structure has shown that the vapor phase contribution to the effective diffusivity is particularly efficient on a diffusion time scale corresponding to root mean squared displacements of the order of pores dimension.